Ferroptosis is Involved in Hypoxic-ischemic Brain Damage in Neonatal Rats. (1st April 2022) - Lin, Wei; Zhang, Tianlei; Zheng, Jinyu; Zhou, Yiyang; Lin, Zhenlang; Fu, Xiaoqin
Highlights: Ferroptosis is involved in the process of HIBD in neonatal rats. After HIBD, the decrease of antioxidant capacity induces ferroptosis. Iron overload induces ferroptosis participation in HIBD. Ferroptosis induced after HIBD may through the System Xc--GSH-GPX4 functional axis. Abstract: Ferroptosis is an iron-dependent form of regulated cell death, which is driven by loss of activity of the lipid repair enzyme glutathione peroxidase 4 (GPX4) and subsequent accumulation of lipid peroxidation. Ferroptosis is implicated in various diseases involving neuronal injury. However, the role of ferroptosis in hypoxic-ischemic brain damage (HIBD) has not been elucidated. The objectives of this study were to evaluate whether ferroptosis is involved in hypoxic-ischemic brain damage and its mechanisms through the HIBD model. A 7-day-old male Sprague-Dawley neonatal rat HIBD model was established by blocking the left common carotid artery. Laser speckle contrast imaging, immunohistochemical staining, transmission electron microscopy were used to measure the effects of ferroptosis on HIBD. Brain tissue on the damaged side in the HIBD group showed atrophied, even liquefied, glial cells increased, and blood perfusion was significantly reduced. The HIBD group insult significantly increased reactive oxygen species levels, as well as the protein levels of iron metabolism-related proteins transferrin receptor (TFRC), ferritin heavy chain (FHC), and ferritin light chain (FLC), while reducing the levels of Solute Carrier Family 7 Member 11 (SLC7A11), glutathione (GSH), and GPX4. These changes resulted in diminished cellular antioxidant capacity and mitochondrial damage, causing neuronal ferroptosis in the cerebral cortex. We conclude that ferroptosis plays a role in HIBD in neonatal rats. Ferroptosis-related mechanisms such as abnormalities in iron metabolism, amino acid metabolism, and lipid peroxidation regulation play important roles in HIBD.